A Review of Benign Subcutaneous Emphysema Following Knee Arthroscopy - Ike, Robert W. (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
Objective: Describe patients developing subcutaneous edema after knee arthroscopy. Methods: Personally encountered reported case plus searches using PubMed, Scopus, Web of Science of “subcutaneous edema” and “arthroscopy”. Results: Of 11 cases, 4 could be traced to mishaps during the arthroscopic procedure and two others to non-healing wounds. Edema ranged from chest wall to ankle, and usually appeared several days after arthroscopy. Patients appeared well and did not motivate treatment for gas gangrene, except in one case that underwent fasciotomy and another an arthrotomy. Recovery was complete within 2 days to 3 weeks, with no residual effect on the operated knee. Reported subcutaneous edema follows shoulder arthroscopy more often than knee arthroscopy, and can also complicate arthroscopy of hip and elbow. Conclusion: Subcutaneous edema is a rare dramatic complication of knee arthroscopy with a benign outcome.